Pengaruh Kompensasi Dan Motivasi Terhadap Kinerja Karyawan CV. New Global Glass Di Kabupaten Majalengka - Ipah Hernipah; Dani Ahmad Hamdani (Humantech : Jurnal Ilmiah Multidisiplin Indonesia, 2022)
Human resource management is a central factor in an organization. Whatever the form and purpose, the organization is made based on various visions for the benefit of humans and in carrying out its mission it is managed and managed by humans. Thus, the focus of the study of human resource management is on issues related to human labor. Compensation and motivation problems can affect employee performance. The object of this research is the employees of CV New Global Glass in Majalengka Regency. The research method used is descriptive and verification methods. The sample in this study were 90 respondents using saturated sampling. Data collection techniques are using questionnaires, interviews and observations. Data instrument testing is done by means of validity test, reliability test, data normality test, correlation coefficient analysis, regression coefficient analysis, coefficient of determination analysis, and hypothesis testing. The results of this study indicate that: (1) the compensation for CV New Global Glass in Majalengka Regency has reached more than 75%, which is proven, namely 87.5% or tcount > ttable (82,720 > 1,662). (2) The motivation for CV New Global Glass in Majalengka Regency has reached more than 70%, which is proven, namely 86.5% or tcount > ttable (96.074 > 1.662). (3) The performance of employees at CV New Global Glass in Majalengka Regency has reached more than 60%, which is proven, namely 89.5% or tcount > tcount (92,910 > 1,662). (4) Compensation has a positive and significant effect on employee performance at CV New Global Glass in Majalengka Regency, because tcount > ttable (7.387 > 1.662). (5) Motivation has a positive and significant effect on employee performance at CV New Global Glass in Majalengka Regency, because (5.533 < 1.662). (6) Compensation and motivation together have a significant effect on CV New Global Glass in Majalengka Regency, because the F value is 155.597 with a probability level of 0.000 which is smaller than alpha 0.05. In conclusion, compensation and motivation have a positive effect and a significant change on employee performance. Suggestions need to be carried out further research on other factors that affect employee performance that are not examined by the author.